Numerical Heat Transfer and Fluid Flow Select Proceedings of NHTFF 2018 - Srinivasacharya, D.; Reddy, K. Srinivas; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book comprises selected papers from the International Conference on Numerical Heat Transfer and Fluid Flow (NHTFF 2018), and presents the latest developments in computational methods in heat and mass transfer. It also discusses numerical methods such as finite element, finite difference, and finite volume applied to fluid flow problems. Providing a good balance between computational methods and analytical results applied to a wide variety of problems in heat transfer, transport and fluid mechanics, the book is a valuable resource for students and researchers working in the field of heat transfer and fluid dynamics.
1. Finite element, finite difference, finite volume and spectral methods -- 2. Fluid mechanics, heat transfer and thermodynamics -- 3. Multiphase and non-Newtonian fluid flows -- 4. Micropolar, couple stress and nanofluid flows -- 5. Bio-fluid mechanics -- 6. Numerical methods in fluid flow and heat transfer -- 7. Transport phenomena in porous media.
Keywords: Fluid mechanics; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Mathematical physics; Engineering Fluid Dynamics; Engineering Thermodynamics, Heat and Mass Transfer; Theoretical, Mathematical and Computational Physics